Phase diagram of a current-carrying superconducting film in absence of the magnetic field - Bezuglyi, E.V.; Zolochevskii, I.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
It is present the phase diagram for the current states of superconducting films, based on the experimental investigation of the resistive transitions induced by the transport current. It is found that a comparatively narrow film with the width w < 5λ^ (T) (λ^ is the penetration depth of the magnetic field) never enters the vortex state, but experiences direct transition from the purely superconducting state to the resistive state with phase-slip centers as soon as the current exceeds the critical Ginzburg–Landau current IcGL. The Meissner current state of the films of intermediate width, 5λ^(T) < w < 10λ^(T), transforms at I > 0.8IcGL to the vortex resistive state which exists within the current interval 0.8IcGL < I < Im, where the value of the upper critical current is in a good agreement with the heory. The vortex state of wide films, w > 10λ^, is realized within the current region IcAL < I < Im, where IcAL is the transition point to the vortex state calculated for the limiting case w >> λ ^. At I > Im, the films with the width w > 5λ^(T) enter a vortex-free resistive state with phase-slip lines.